Differences between disease-associated endoplasmic reticulum aminopeptidase 1 (ERAP1) isoforms in cellular expression, interactions with tumour necrosis factor receptor 1 (TNF-R1) and regulation by cytokines. (14th April 2015) - Yousaf, N; Low, W Y; Onipinla, A; Mein, C; Caulfield, M; Munroe, P B; Chernajovsky, Y
Summary: Endoplasmic reticulum aminopeptidase 1 (ERAP1) processes peptides for major histocompatibility complex (MHC) class I presentation and promotes cytokine receptor ectodomain shedding. These known functions of ERAP1 may explain its genetic association with several autoimmune inflammatory diseases. In this study, we identified four novel alternatively spliced variants of ERAP1 mRNA, designated as ΔExon-11, ΔExon-13, ΔExon-14 and ΔExon-15. We also observed a rapid and differential modulation of ERAP1 mRNA levels and spliced variants in different cell types pretreated with lipopolysaccharide (LPS). We have studied three full-length allelic forms of ERAP1 (R127-K528, P127-K528, P127-R528) and one spliced variant (ΔExon-11) and assessed their interactions with tumour necrosis factor receptor 1 (TNF-R1) in transfected cells. We observed variation in cellular expression of different ERAP1 isoforms, with R127-K528 being expressed at a much lower level. Furthermore, the cellular expression of full-length P127-K528 and ΔExon-11 spliced variant was enhanced significantly when co-transfected with TNF-R1. Isoforms P127-K528, P127-R528 and ΔExon-11 spliced variant associated with TNF-R1, and this interaction occurred in a region within the first 10 exons of ERAP1. Supernatant-derived vesicles from transfected cells contained the full-length and ectodomain form of soluble TNF-R1, as well as carrying the full-length ERAP1 isoforms. We observed marginal differences between TNF-R1 ectodomain levels when co-expressed with individual ERAP1 isoforms, and treatment of transfected cells with tumour necrosis factor (TNF), interleukin (IL)-1β and IL-10 exerted variable effects on TNF-R1 ectodomain cleavage. Our data suggest that ERAP1 isoforms may exhibit differential biological properties and inflammatory mediators could play critical roles in modulating ERAP1 expression, leading to altered functional activities of this enzyme.